Logistics outsourcing in large manufacturing companies - Budler, Marko (Economic and business review, 2021)
Logistics outsourcing is a mode of operation for companies in global supply chains that have been increasingly devoting more attention to their core activities. This study examines the state-of-the-art in logistics outsourcing in the Slovenian manufacturing industry. Additionally, the authors benchmark the findings against a similar study from 2013. Finally, this study provides a discussion of logistics-outsourcing specifics in some countries with the use of secondary data. We identify transportation as a top-ranked logistics activity, and a general propensity for higher-level logistics outsourcing (e.g. 4 PL). The authors contribute to the supply-chain management society by identifying the drivers of, barriers to, and activities in logistics outsourcing.
Keywords: industrial organization; industrijsko podjetje; international comparisons; logistics; logistika; mednarodne primerjave; Slovenia; Slovenija